2019
DOI: 10.3926/jotse.539
|View full text |Cite
|
Sign up to set email alerts
|

The effect of using flipped teaching in project management class for undergraduate students

Abstract: Teaching Project Management module to undergraduate students is important and has been globally considered in multiple academic disciplines by many higher institutions. Students in undergraduate level encounter difficulty in understanding the topic of project management since there have no prior knowledge before the course. This paper aimed to determine the effectiveness of flipped teaching and active learning in Project Management module for undergraduate students in Civil Engineering. However, the paper disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
4
1
2
Order By: Relevance
“…So, future researchers may do more research to investigate the influence of other variables on basic-learning skill. The result was not consistent with some previously reported works, who argued that assessment impact influence basic-learning skill scores (Abushammala, 2019;Brosvic et al, 2006;Chen, 2006;Karagiannopoulou & Christodoulides, 2005;Kizito et al, 2016;Lee & Chen, 2014;Lees & Anderson, 2015;Pinto & Fernández-Pascual, 2017;Prevost et al, 2018). In conclusion, H # 4: The higher assessment impact scores are associated with higher basic-learning skill scores, is been rejected.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…So, future researchers may do more research to investigate the influence of other variables on basic-learning skill. The result was not consistent with some previously reported works, who argued that assessment impact influence basic-learning skill scores (Abushammala, 2019;Brosvic et al, 2006;Chen, 2006;Karagiannopoulou & Christodoulides, 2005;Kizito et al, 2016;Lee & Chen, 2014;Lees & Anderson, 2015;Pinto & Fernández-Pascual, 2017;Prevost et al, 2018). In conclusion, H # 4: The higher assessment impact scores are associated with higher basic-learning skill scores, is been rejected.…”
Section: Discussioncontrasting
confidence: 83%
“…Assessment methods and matriculation examination score were the predictors of students' progress (Karagiannopoulou & Christodoulides, 2005;Kizito et al, 2016). Duzhin and Gustafsson (2018) found that online homework with immediate feedback was found to be even more effective than clickers, as well as Abushammala (2019) indicates that the use of multiple in-class activities and digital technology are important to enhance students' performance. Lees and Anderson (2015) pointed out that formative assessment may improve student performance, and Brosvic, Dihoff, Epstein, and Cook (2006) revealed that feedback facilitates the acquisition of mathematics knowledge.…”
Section: Relationship Between Assessment Impact and Basic-learning Skillmentioning
confidence: 99%
“…We were able to verify that the implementation of the inverted methodology carried out with this group of high school students was highly satisfactory. This pedagogical approach is born in the university environment, and its applicability and effectiveness in that context seem more than evident (Abushammala, 2019;Davies et al, 2013;Eldy, Chang, Butai, Basri, Awang, Din et al, 2019;González-Gómez et al, 2017;Herreid & Schiller, 2013;Jeong et al, 2018;Knight & Wood, 2005;Love et al, 2013;Mason et al, 2013;Mattis, 2015;Torrecilla, 2018), however, at pre-university educational levels, where there are no hours in the curriculum dedicated to personal work and/or at home, its implementation is more complicated. The reverse learning model, like any other type of non-traditional learning, requires a substantial change in the mentality of the students and a radical change in class dynamics, aspects that must be carried out gradually so that students can adapt to them and become protagonists of their own learning process.…”
Section: Students' Performancementioning
confidence: 99%
“…In this study, students pointed out that the computer technician was not always available to start the classes by linking up the students, resulting in lessons being delayed or cancelled altogether. In addition, proper classroom management and monitoring of students during IVT is vital to enhance their learning (Abushammala, 2019). Similarly, Lee et al (2016) suggest that it is vital that technical support be offered to students in future to improve learning.…”
Section: Challenges Experienced In the Use Of Ivt As A Mode Of Teachingmentioning
confidence: 99%